The Coronavirus Pandemic (SARS-CoV-2): New Problems Demand New Solutions, the Alternative of Mesenchymal (Stem) Stromal Cells - Eiro, Noemi; Cabrera, Jorge Ruben; Fraile, Maria; Costa, Luis; Vizoso, Francisco J. (Frontiers in Cell and Developmental Biology, 2020)
Mesenchymal (stem) stromal cells (MSC) can be a therapeutic alternative for COVID-19 considering their anti-inflammatory, regenerative, angiogenic, and even antimicrobial capacity. Preliminary data point to therapeutic interest of MSC for patients with COVID-19, and their effect seems based on the MSC’s ability to curb the cytokine storm caused by COVID-19. In fact, promising clinical studies using MSC to treat COVID-19, are currently underway. For this reason, now is the time to firmly consider new approaches to MSC research that addresses key issues, like selecting the most optimal type of MSC for each indication, assuming the heterogeneity of the donor-dependent MSC and the biological niche where MSC are located.